2012
DOI: 10.1002/pros.22633
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of synergism between antagonists of growth hormone‐releasing hormone and antagonists of luteinizing hormone‐releasing hormone in shrinking experimental benign prostatic hyperplasia

Abstract: GHRH antagonist and LHRH antagonist combination potentiates rat prostate weight reduction and synergistically inhibits of growth of BPH-1 leading to cell cycle arrest in S-phase. These effects were lesser in normal stromal prostate cell line, WPMY-1. Our findings suggest that GHRH antagonists could be useful for BPH therapy, possibly in combination with LHRH antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
1
17
0
1
Order By: Relevance
“…The expression of protein for GHRH and GHRHRs was markedly elevated in this model, indicating the involvement of the GHRH autostimulatory loop in the pathogenesis of hormone-induced prostatic enlargement (36). In this experimental model, antagonists of GHRH, synthesized in our laboratories, demonstrated beneficial effects on prostate size, mitotic index, and the expression of various growth factors, inflammation-related genes, and key regulators of EMT (36)(37)(38).…”
Section: Significancementioning
confidence: 69%
“…The expression of protein for GHRH and GHRHRs was markedly elevated in this model, indicating the involvement of the GHRH autostimulatory loop in the pathogenesis of hormone-induced prostatic enlargement (36). In this experimental model, antagonists of GHRH, synthesized in our laboratories, demonstrated beneficial effects on prostate size, mitotic index, and the expression of various growth factors, inflammation-related genes, and key regulators of EMT (36)(37)(38).…”
Section: Significancementioning
confidence: 69%
“…Hypothalamic neurohormone GHRH and GHRH-R are not confined to the hypothalamic-pituitary axis, however, but are also produced by various extrahypothalamic sites. GHRH/GHRH-R modulates cell proliferation and apoptosis in many tissues, including prostate (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…We also showed that neurohormones including growth hormone-releasing hormone (GHRH) and luteinizing hormone-releasing hormone (LHRH) can act as growth factors in experimental BPH. Potent synthetic antagonists of GHRH and of LHRH cause marked shrinkage of experimental BPH by direct inhibition of prostatic GHRH and LHRH and by suppression of proinflammatory IL-1β, NF-κβ/p65, and COX-2 and various other growth factors and inflammatory cytokines (27)(28)(29)(30).…”
mentioning
confidence: 99%